The 2024 Reclaim the Night Movement Following the Kolkata Rape and Murder Case: A Framing Theory Analysis - Muhammad Erza Aimar Rizky; Timothy Sandro Yusuf; Josepha Caroline Sekarningrum Rijadi; Muhammad Dafa Ramadhan; Ghazy Abiyyu Dary Adhipramana (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2025)
The “Reclaim the Night” (RTN) movement in India, galvanized by the 2024 Kolkata rape and murder case, exemplifies the dynamic interaction between grassroots activism and collective action framing in addressing systemic gender-based violence. This study investigates the dynamics of the collective action framing process within the 2024 "Reclaim the Night" demonstrations following the rape and murder of a female doctor in Kolkata. Employing Benford and Snow's collective action framing theory, the research qualitatively analyzes the movement's diagnostic, prognostic, and motivational framing, along with influencing variables and discursive, strategic, and contested processes. Findings indicate that diagnostic framing effectively identified widespread issues, including victim stigmatization and systemic political failures rooted in patriarchal perspectives. Prognostic framing emphasized actionable solutions such as proper legal processes and improved working conditions to prevent future tragedies. Motivational framing leveraged public frustration with legal authorities' neglect to amplify protest momentum. The RTN movement's strategic use of master frames like safety, freedom, and government accountability, coupled with social media mobilization, garnered significant support. However, contested processes, including public and political counter-arguments, highlight the ongoing challenges in reframing societal narratives. This movement offers a model for transformative action, contributing to a broader vision of gender equality by reclaiming public spaces and reconstructing societal narratives.